2012
DOI: 10.1021/es2026399
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Performance of Algal Biofuel Technology Options

Abstract: Considerable research and development is underway to produce fuels from microalgae, one of several options being explored for increasing transportation fuel supplies and mitigating greenhouse gas emissions (GHG). This work models life-cycle GHG and on-site freshwater consumption for algal biofuels over a wide technology space, spanning both near- and long-term options. The environmental performance of algal biofuel production can vary considerably and is influenced by engineering, biological, siting, and land-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(105 citation statements)
references
References 9 publications
5
98
1
1
Order By: Relevance
“…Additionally, much of the biomass energy is not recovered as liquid fuel but remains in the LEA. Finally, wet extraction processes have not been demonstrated, yet dry processes require excessive drying energy (Vasudevan et al 2012).…”
Section: Context and Motivationmentioning
confidence: 99%
“…Additionally, much of the biomass energy is not recovered as liquid fuel but remains in the LEA. Finally, wet extraction processes have not been demonstrated, yet dry processes require excessive drying energy (Vasudevan et al 2012).…”
Section: Context and Motivationmentioning
confidence: 99%
“…These types of conversions were applied for decanters ( [18]; [19]) and belt filters ( [18]; [20]). Other conversions were based on the reported amount of CO2 emissions per ton biodiesel for disk stack centrifugation ( [21]; [20]; [22]), decanters ( [18]; [19]), chamber filters ( [21]; [19]), inorganic flocculation ( [23]; [24]; [25]) and organic flocculation ( [26]; [24]). This approach allowed to estimate the amount of greenhouse gas emissions based on literature data across several studies and report it as an interval between minimum and maximum reported values.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Embora, os custos associados à filtração são baixos, o entupimento da tela e membrana devido à incrustação limita sua adequação à maioria das espécies de microalgas (SINGH; DHAR, 2011). Na colheita da biomassa os processos podem ser aplicados em conjunto como a floculação e posterior centrifugação, sendo uma forma mais viável de realizar o processo (VASUDEVAN et al, 2012;SORATANA;HARPER;LANDIS, 2012).…”
Section: Processo De Colheita Da Biomassaunclassified